2006
DOI: 10.1002/pssc.200562745
|View full text |Cite
|
Sign up to set email alerts
|

Interference quantum corrections in the low temperature microwave magnetoresistance of the nondegenerate Ge

Abstract: The first observation of low temperature magnetoresistance (MR) of interference nature in the case of a light doping is reported. This MR occurs in both n‐ and p‐type Ge samples in weak magnetic fields at frequency of 10 GHz and temperatures below 30 K. It is registered on the background of the classical MR effect associated with electrons in different valleys of n‐Ge and with different (heavy and light) holes of p‐Ge. (© 2006 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 2 publications
1
8
0
1
Order By: Relevance
“…Our experiments demonstrated that, indeed, the minima related to light and heavy holes are separately observed at low temperatures, as it has been shown previously [2,3]. In addition, it was found that the field dependences of the MA are different for samples rotated in the (211) and (110) planes.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Our experiments demonstrated that, indeed, the minima related to light and heavy holes are separately observed at low temperatures, as it has been shown previously [2,3]. In addition, it was found that the field dependences of the MA are different for samples rotated in the (211) and (110) planes.…”
Section: Resultssupporting
confidence: 88%
“…We have shown previously [1][2][3] that the averaging of the hole effective mass in lightly doped p-Ge occurs during a time comparable with the energy scattering time, rather than with the momentum scattering time, as it has been believed so far [4]. Our conclusion was based on measurements of the dependence of the microwave energy absorption (frequency 10 10 Hz) on the magnetic field at low temperatures [magnetoabsorption (MA)].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…1 Introduction Previously, we have reported an observation of the negative magnetoresistance (MR) [positive magnetoconductance (MC)] in lightly doped (nondegenerate) Ge at low temperatures in the microwave frequency range (~10 GHz) [1,2]. This was done using the electron spin resonance (ESR) method, which records the derivative of the microwave absorption with respect to magnetic field, proportional, in samples with high resistance, to the derivative of MC, dP/dH ~ dσ/dH.…”
mentioning
confidence: 99%
“…In this case, the change of sign by the derivative is due to specific physical features of the field dependence of MC and will be considered below. Figure 1 Field dependence of the microwave absorption, measured with the ac modulating magnetic field switched (1) on and (2) off at T = 14 K. Figure 2 shows field dependences of the MC derivative at different temperatures for the p-Ge sample with p ≈ 3×10 14 cm -3 early investigated in [1,2]. The curves are normalized in such a way that the minimum value of the derivative is unity at all temperatures.…”
mentioning
confidence: 99%